(untitled) (American Journal of Innovation in Science and Engineering, 2024)
The Lagdo hydropower plant is the smallest of three plants designed before the 1990s in Cameroon. It has a capacity of 72 MW and is the main source of energy for the North Interconnected Network (NIN). This facility has been experiencing several problems over the past ten years and is increasingly unsatisfactory in terms of service. This is due to several parameters, including the instability observed in the flow structure. In this paper, we have evaluated some parameters that may be at the origin of these instabilities by a numerical approach, followed by field observations. It appears from this study that in addition to the dynamic field variation parameter (pressure and velocity) involved in the creation and propagation of instabilities, others, such as the water level in the upstream reservoir and the variation of the turbulent friction, are also to be considered.